THE IMPACT OF INSTRUCTIONAL MATERIALS ON STUDENTS’ ACADEMIC PERFORMANCE IN ENGLISH LANGUAGE IN JUNIOR SECONDARY SCHOOL, YOBE STATE - FATIMA YUSUF; GAMBO ABDULLAHI JINJIRI (Innovare Journal of Social Sciences, 2024)
The study investigated the impact of instructional materials on student’s academic performance using the English language in a junior secondary school in Yobe State. The study employed self-designed multiple-choice using structural equation modeling to assess and test the relationship between the variables. The population strictly targeted junior secondary school students, of which 230 were sampled. Specialists validated the instrument in the subject area based on the measurement and educational management. The structural equation modeling statistical tool is used to analyze the collected data. The findings indicate a significant relationship between instructional material and student’s academic performance in the pre-test and post-test of students in the experimental group. It is also assumed that students who taught using instructional materials performed better than those taught without.